'Manjago Partuturan" Efforts To Preserve Cultural Heritage In Batak Ethnic Pariban Marriage - Kaloko, Indah Sahmauli Indriyani; Dora, Nuriza (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Manjago Partuturan" is a kinship genealogy of the Batak tribe. Where this speech is very important as a determinant of the kinship system of our clan in the Batak community in order to continue the bloodline of the clan. 'Pariban' which is often used by Batak people. Pariban itself refers to cousins. A boy will call 'Pariban' to the daughter of Tulang (Tulang means uncle, mother's brother), and conversely a girl will call 'Pariban' to the son of her Namboru (Namboru means brother father's women, both father's brothers and sisters). Biological marpariban refers to the cousin relationship between men and women in the Toba Batak tribe. The term "pariban" is often used by Batak people. This is widely discussed because it is related to the traditions, genealogy, and also the personality of the Batak people. Many people consider the "pariban" phenomenon to be an ancient Batak term which is no longer practicable at this time. Some people know that Pariban is a tradition inherited from ancient Batak people's unique matchmaking and is sometimes no longer considered rational. The aim of the research is to find out about ethnic Batak pariban marriages in society, to find out the values of pariban marriages, and so on. According to Lofland and Lofland as quoted by Lexy. J. Moleong (2000) in his book entitled Qualitative Research Methodology, stated that the main data sources in qualitative research are words and actions, the rest is in the form of additional data such as documents and so on. According to Lofland and Lofland as quoted by Lexy. J. Moleong (2000) in his book entitled Qualitative Research Methodology, stated that the main data sources in qualitative research are words and actions, the rest is in the form of additional data such as documents and so on. Pariban is a cousin. A boy will call "pariban" to the daughter of Tulang (Tulang = uncle, mother's brother), and conversely a girl will call "pariban" to the son of her Namboru (Namboru = brother father's women, both father's brothers and sisters) This effort covers various aspects, such as carrying out traditional ceremonies at weddings, strengthening kinship relations, preserving the Batak language, and cultural education for the younger generation.